5n+8-1n=6(1n-1)

Simple and best practice solution for 5n+8-1n=6(1n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+8-1n=6(1n-1) equation:


Simplifying
5n + 8 + -1n = 6(1n + -1)

Reorder the terms:
8 + 5n + -1n = 6(1n + -1)

Combine like terms: 5n + -1n = 4n
8 + 4n = 6(1n + -1)

Reorder the terms:
8 + 4n = 6(-1 + 1n)
8 + 4n = (-1 * 6 + 1n * 6)
8 + 4n = (-6 + 6n)

Solving
8 + 4n = -6 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
8 + 4n + -6n = -6 + 6n + -6n

Combine like terms: 4n + -6n = -2n
8 + -2n = -6 + 6n + -6n

Combine like terms: 6n + -6n = 0
8 + -2n = -6 + 0
8 + -2n = -6

Add '-8' to each side of the equation.
8 + -8 + -2n = -6 + -8

Combine like terms: 8 + -8 = 0
0 + -2n = -6 + -8
-2n = -6 + -8

Combine like terms: -6 + -8 = -14
-2n = -14

Divide each side by '-2'.
n = 7

Simplifying
n = 7

See similar equations:

| X*x*2=122 | | 3(2b-4)+6=2(3b-6) | | -(2x-5)-(2x-5)+4=6(x-1)-(2x+7)+3 | | 2x-1/x=4/3 | | 6(a+3)=9 | | 5x^2-37=43 | | 5x+7/3=2x+9 | | xy^3/y^5 | | x+15+x=x+45+x+40+x+25 | | (9n^6)^(1/2) | | 4=u+6 | | 40a^2+195+140=0 | | 8xy^3/6y^5 | | 4X-3=2-6X | | x^2-21x-216=0 | | (n+6)((n+6)-10)=200 | | -(7x-3)-(4x-5)+11=-3(x-1)-(11X+2)+3 | | 8x^204=28 | | (n^(-4/15))*(5n^(3/5)) | | 3/75=x/10 | | 6y+(3y+3)=16 | | n^-4/15*5n^3/5 | | -5m^2+245=0 | | ln(3x+1)+ln(x)=ln(2) | | 3(2y+3)=-3y-9 | | Y=-16x^2+384 | | 3n+5forn=4 | | 5x-1.2=9x-.8 | | 4+4-6x=35 | | 3(2x-1)=5x+2 | | 7/14= | | (-5/6)y(-3/4) |

Equations solver categories